PENGARUH KOMPETENSI SUMBER DAYA MANUSIA, SISTEM INFORMASI AKUNTANSI, DAN SISTEM PENGENDALIAN INTERNAL TERHADAP KINERJA KEUANGAN KOPERASI SIMPAN PINJAM KOPDIT OBOR MAS ( STUDI EMPIRIS PADA KSP KOPDIT OBOR MAS) - Mirawati, Elisabeth; Pati Sanga, Konstantinus; De Romario, Fransiscus (Universitas Nusa Nipa Maumere, 2025)
This research aimed to determine the influence of human resource competence, accounting information systems, and internal control systems on financial performance at Obor Mas Credit Union. The research used a quantitative approach with a population of 110 permanent employees of Obor Mas Credit Union, while the sample was determined to be 52 respondents using the Slovin formula. Data were obtained through questionnaires distributed to respondents and processed using multiple linear regression analysis with the aid of statistical software. The research results indicated that human resource competence, accounting information systems, and internal control systems, both partially and simultaneously, did not have a significant impact on cooperative financial performance. This finding confirmed that improved financial performance was not solely determined by these three internal factors but rather requires more comprehensive strategic planning and managerial policies. This research was expected to contribute theoretically to the development of accounting science and serve as a practical consideration for credit union managers in improving the effectiveness of financial management.